Digital Economy - Some Ethical Aspects - Dramalieva, Valentina (Research Papers, 2020)
The first part of the text outlines the nature and specifics of the digital economy, presenting basic and related concepts and terms by which it is explored worldwide. The second part finds the preconditions for the ethical side of the digital reality in that nothing happens spontaneously there, but requires focused efforts and adaptation at all levels, which forces subjects to make choices, take decisions, and be responsible for their reasonable activities. The third part outlines typical ethical issues; systematizes basic ethical values and principles that can reliably be used as criteria for assessing the ethical correctness in the digital environment; points 20 current questions raised by ethical analysis. The conclusion is a brief summary and conclusions of reasoning.
Keywords: Technological change; Industry 4.0; Ethical aspect of digital economy; Ethical values and principles for digital economy analysis; Technological risk; Digital economy